Analisa Efektivitas Metode Octave Allegro dan Fmea Dalam Penilaian Risiko Aset Informasi Pada Institusi Pendidikan Tinggi - Adib Pakarbudi; Dea Tiara Piay; Dita Nurmadewi; Andy Rachman (STMIK Budi Darma, 2023)
The current rapid development of technology allows all tertiary institutions to utilize information systems to support their operations, such as the Surabaya ABC Institute of Technology. Through the Central Information System Unit (PSI), the ABC Surabaya Institute of Technology can develop and manage ICT (Information and Communication Technology) so that it can easily manage various kinds of data and information. However, it should be noted that currently digital information is an important asset that needs to be protected from various kinds of adverse risks. But unfortunately the application of information asset risk management at the Surabaya ABC Institute of Technology has not been implemented properly. From these problems, the researcher aims to find out the process of managing the security of information assets in tertiary institutions through a risk assessment of the information assets they have. To achieve this goal the research method used refers to the Octave Allegro framework and the FMEA method is used to assess the risk of information assets. The results of this study indicate that the ABC Institute of Technology has 11 important assets which are divided into 5 categories, namely: Data, Hardware, Network, Software, People. Of the eleven assets, six of them have a high level of risk. From these findings it can be concluded that universities also need to manage information security. These results also indicate that the method used by researchers is very helpful in determining the risk of the value of information assets owned by the ABC Surabaya Institute of Technology. So that the combination of the Octave Allegro method with the FMEA method is very effective in helping organizations carry out information security management.